Calcite dissolving bacteria from peanut (Arachis hypogaea) pegging zone influences soil calcium level - Peper, Alan; Brenneman, Timothy; Yang, Li (Frontiers in Microbiomes, 2022)
Microbial communities play critical roles in mobilizing soil nutrition and, consequentially, shaping plant growth and stress responses. Soluble calcium in the pegging zone is essential for peanut yield. Calcium starvation may lead to seed abortion and increased incidence of disease, such as pod rot. Currently, gypsum or lime are often used to supplement calcium in the pegging zone. Calcite Dissolving Bacteria (CDB) can dissolve poorly soluble calcite into Ca2+ thus making it available to plants. Here, we report the isolation and characterization of CDB from a peanut field in Tifton, Georgia. We identified 65 CDB isolates, representing 15 unique strains belonging to 10 different genera. When applied to field soil, most of these CDB survived only several days. However, a synthetic community of CDB strains increased soluble calcium levels when applied to field soil. We also found that CDB abundance was negatively associated with a soluble calcium level in soil. In summary, we conclude that CDB has the capacity to influence calcium availability in soil, and the abundance of CDB in a bacterial community dynamically respond to soil calcium levels.